First islanders prehistory and human migration in Island Southeast Asia /cPeter Bellwood ; with invited contributions by (in order of appearance) Colin Groves, Debbie Argue, Hirofumi Matsumura, Marc Oxenham, Truman Simanjuntak, Mariko Yamagata, Murray Cox, Philip J. Piper, Robert Blust, Daud Aris Tanudirjo, Hsiao-chun Hung and Mike T. Carson - Bellwood, Peter S. (John Wiley & Sons, Inc., 2017)
Arbitration is the favoured method of dispute resolution in international construction projects. These projects invariably involve a multitude of parties coming from different jurisdictions and bound by numerous, most often bilateral, contracts. Disputes between the parties to such bilateral contracts frequently have repercussions for other parties. For example, an employer's claim for defective work against a main contractor can then trigger a related main contractor's claim against the subcontractor who ultimately caused the defects